PENGARUH DAYA TARIK, HARGA, DAN LOKASI TERHADAP KEPUASAN KONSUMEN - Farisa, Indri; Mulyati, Awin; Maruto, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2018)
A tourism must have their own strategy in running business both in terms of attractiveness, price, location, and so forth, so that consumers interested in visiting and satisfied after a visit. It is expected that these consumers can re-puchase and recommend to others to visit.This study aims to determine the effect of Atractiveness, Price, and Location of tourism to Consumer Satisfaction in Agrowisata Petik Jeruk Sumbersono. Population used in this research is all people who ever come to Agrowisata Petik Jeruk Sumbersono. The sample used by 100 respondents who ever come to Agrowisata Petik Jeruk Sumbersono by using accidental sampling technique. Data were collected through questionnaires distributed by visitors who cameto Agrowisaata Petik Jeruk Sumbersono and interviewed to the manager related to company profile. Data analyze using Validity Test, Reliability Test, Multicolinierity Test, Multiple Regression Test, Correlation Test, Partial Test (t), Simultaneous Test (F), and Determination Coefficient Test (R2).The results of this study indicate that the Attractiveness has a positive and significant effect on Customer Satisfaction, Price has a positive and significant effect on Customer Satisfaction, and Location has a positive and significant effect on Customer Satisfaction of Agrowisata Petik Jeruk Sumbersono. Attractiveness, Price and Location simultaneously influence on Customer Satisfaction of Agrowisata Petik Jeruk Sumbersono. The Location has a dominant influence on the Customer Satisfaction of Agrowisata Petik Jeruk Sumbersono.Keywords: attractiveness, price, location, customer satisfaction